AB0623 Treatment of Scleroderma-Related Digital Ulcers with Iloprost: A Cohort Study. (15th July 2016) - Colaci, M.; Lumetti, F.; Giuggioli, D.; Guiducci, S.; Ballando Randone, S.; Fiori, G.; Matucci-Cerinic, M.; Ferri, C.
Abstract : Background: SSc is characterized by diffuse microangiopathy leading digital ulcers (DU) in almost 50% of patients. The treatment of non-healing DU is often very difficult. It includes both systemic (prostanoids, bosentan) and local (wound care) therapies. In clinical practice, therapy of DU should be tailored mainly on clinical symptoms and according to specific clinician's experience. At the moment, no guidelines for the use iloprost, a stable prostacyclin-analogue used for the management of DU in SSc, are not yet available. Objectives: We report the therapeutical effects of our regimen for the use of iloprost in a cohort of SSc patients during a long-lasting follow-up period. Methods: Fifty consecutive SSc patients recruited at two Rheumatology Units since January 2003, who received iloprost infusions for a time period >2 years were included in the analysis. Patients' features were: males/females ratio 7/43; mean age at SSc diagnosis 43.5±12.7SD years; median disease duration at the beginning of therapy 2 years (range 0–18); mean follow-up with iloprost treatment 10±4.2SD years; diffuse SSc cutaneous subset in 13/50 (30%) patients; anti-Scl70 and anticentromere autoantibodies in 25 (50%), and 14 (28%) subjects, respectively. For all patients epidemiological, clinical, laboratory, and instrumental data were available for the study period. Iloprost schedule consisted in monthly i.v. infusion at 0.8–1 ng/kg body weight/min with average cumulative dosage per each session of 25 μg, according to patients' tolerance. At the beginning of the treatment and in the presence of recent onset, severe and/or multiple DU at high risk of gangrene, patients were hospitalized for continuous infusion of iloprost (3 days, average 0.2 mg). Results: 31/50 (62%) patients showed DU at the beginning of iloprost therapy: among them, 22 (71%) resolved during the follow-up, while the other 9 presented recurrent or chronic DU, despite the treatment. With regards the 19/50 patients without DU at baseline, only one developed skin lesions at the end of very long follow-up (8 years), when a general deterioration of clinical conditions, in particular severe pulmonary hypertension, lead to exitus. Considering the 31 SSc patients with DU at baseline, a diffuse skin subset was present in 3 out of 22 patients with healed DU, and in 5 out of 9 who did not (13.6% vs 55.5%, Fisher's p=0.027); no other significant correlations were observed as regards visceral organ involvement and serological alterations. Finally, the concomitant administration of other vasoactive therapies seems to be scarcely relevant on the DU outcome. Conclusions: Our data suggest that long term administration of iloprost seems to be effective for DU healing in SSc. Comparative studies with different treatment regimens are warranted to reach a consensus on standardized guidelines for the use of Iloprost for DU healing in SSc. Disclosure of Interest: None declared